Development of the clinical nursing practice guideline on perioperative hypothermia prevention in patients undergoing operation - Padungsak, Sakaewan; Bamrungwong, Suchanun; Khongsamai, Thanida (Thai Journal of Nursing, 2020)
This study aimed to develop the clinical nursing practice guideline (CNPG) for perioperative hypothermia prevention in patients undergoing operation based on the IOWA Model. It comprised 2 steps. Step 1 the development of nursing clinical practice guideline, eight relevant evidences were selected to synthesis the CNPG. This CNPG was composed of nursing care in pre-operation phase, intra-operation phase, and post-operation phase. Step 2 The evaluation of the content validity and its effectiveness. The CNPG of the three phases were as follows. 1) Pre-operation phase, nursing care focused on screening patients at a high risk group and providing active warmer for patient. 2) Intra-operation phase, nursing care focused on providing nursing care to prevent perioperative hypothermia. 3) Post-operation phase, nursing care focused on providing continuous care. After the CNPG implementation in 30 patients for 3 momths, it could prevent perioperative hypothermia in all surgical patients.